Problematika Regulasi Emosi pada Anak dan Pengaruhnya terhadap Interaksi Sosial di Lingkungan Sekolah - Nasywa Azka Aulia; Asma’ul Karimah; Ariqah Izdihar Masyithah; Mochsaf Daffa Arsyanda; Bintang Ksatria Al Giffari; Denok Setyawati; Muhammad Farid Ilhamuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem of emotional regulation in children is a crucial issue in social-emotional development that directly impacts the quality of social interactions in the school environment. Emotional regulation skills serve as the foundation for children to adjust emotional expression, build positive relationships, and navigate various social situations adaptively. However, not all children are able to develop these skills optimally, resulting in various problems such as aggressive behavior (externalization) and anxiety and withdrawal (internalization). This article aims to examine the problem of emotional regulation in children and its impact on social interactions in schools by referring to a literature review of recent research. The method used is a library study analyzing various relevant scientific sources from the past five years. The results of the study indicate that low emotional regulation skills are associated with a decline in the quality of peer relationships, increased social conflict, and the risk of social rejection. In addition, family factors, the school environment, and parenting styles also influence the development of children's emotional regulation. Therefore, schools need to play an active role in developing social-emotional competencies through meaningful, reflective, and collaborative learning to support healthy social interactions.